Mapping Knowledge Structure and Global Research Trends in Gout: A Bibliometric Analysis From 2001 to 2021 - Pengfei Wen; Pan Luo; Binfei Zhang; Yumin Zhang (Frontiers Media S.A., 2022)
BackgroundThe incidence and prevalence of gout have been steadily increasing globally, which has resulted in gout research attracting consistently increased attention. This study aimed to visualize the knowledge structure and research trends in gout research through bibliometrics to help understand the future development of basic and clinical research.MethodsArticles and reviews on gout from 2001 to 2021 were extracted from the Web of Science Core Collection database. CiteSpace and VOSviewer software were used to visualize the knowledge network of countries, institutions, authors, references, and keywords in this field. SPSS and Microsoft Excel software were used for curve fitting and correlation analysis.ResultsA total of 3,259 articles and reviews were included. The number of publications about gout significantly increased yearly. Publications were mainly concentrated in North America, Europe, Oceania, and East Asia. The USA contributed most with 1,025 publications, followed by China and New Zealand. After adjusting for publications by population size and Gross Domestic Product (GDP), New Zealand ranked in the first place. GDP and international collaboration were significantly correlated with scientific productivity for gout research. University of Auckland and Professor Dalbeth Nicola were the most prolific institutions and influential authors, respectively. Rheumatology was the most productive journal for gout research. Gout research hotspots have shifted over time in the following order: clinical features, pathological mechanisms, complications, gouty arthritis, epidemiology, and dual-energy computed tomography to drug clinical trials, which can be observed from the keyword analysis and co-cited reference cluster analysis.ConclusionsThis study found that research on gout is flourishing. The development and experimentation of drugs for the prevention and treatment of gouty arthritis would be the focus of current research and developmental trends in future research.